Transforming into an entrepreneurial university: adaptation and risks; 11th International Technology, Education and Development Conference (INTED2017), 6-8 March, 2017, Valencia, Spain - Brylina I. V. Irina Vladimirovna; Brylin V. I. Vladimir Ivanovich; Khaldeeva M. A. Marina Aleksandrovna; Lutoshkina O. S. Olga Sergeevna (2017, 2017)
Title screen